Paradigma Manajemen Leader dalam Konstruksi Kesalehan Sosial Siswa di MA Shofa Marwa Kabupaten Grobogan - Suwanto Suwanto (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
The management paradigm of a leader is something that cannot be negotiable in supporting the achievement of the goals of Islamic educational institutions, especially for madrasah aliyah. Here the challenge as well as the opportunity for the leader of Islamic educational institutions to be able to realize the expectations of parents and society through a management paradigm that is able to build social piety (hablumminannas), not just individual/religious piety (hablumminallah). This study aims to determine the paradigm of leader management in the construction of social piety. This research uses qualitative research with phenomenological approach, by using descriptive analysis method. Data collection is done by using participative observation techniques, in-depth interviews and documentation. The form of data are the words, notes, reports and documents obtained from the head of the madrasah, deputy head, teachers, and students. Data analysis techniques include data reduction, data presentation, and conclusions. Checking the validity of data is done by extending the presence of researcher, continuous and careful observation, and triangulation techniques using various sources, methods and theories. Based on the analysis of research data obtained conclusion: 1). The paradigm of leader planning in the construction of social piety in MA Shofa Marwa is not in accordance with banghart and trull. 2). The paradigm of the leader's implementation in the construction of social piety in accordance with the statement Anton Athoillah. 3). The leader's evaluation paradigm in the construction of social piety in the MA ShofaMarwa has a finding that does not comply with Kirkpatrick.